Cover Image, Volume 172C, Number 1, March 2016. Issue 1 (March 2016) - Bostwick, Bret; Fang, Ping; Patel, Ankita; Sutton, V. Reid
Abstract : The cover image, by V. Reid Sutton et al., is based on the Research Article Phenotypic and molecular characterization of focal dermal hypoplasia in 18 individuals, DOI:10.1002/ajmg.c.31473 .